Comparison of Financial Performance Badan Amil Zakat Nasional and Lembaga Amil Zakat Nasional - Pramito, Rohman Fajri Jalil; Azwari, Peny Cahaya; Naz'aina, Naz'aina (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to compare and to examine about differences in the performance of zakat management between BAZNAS and Dompet Dhuafa through Financial Performance with purpose to evaluate the success of the institution is to look at how well it performs. The object of this research are the amil zakat institution in Indonesia, namely BAZNAS and Dompet Dhuafa. This study uses a purposive sampling with a descriptive quantitative approach. Data collection in this study is secondary data, which is referring to the annual financial reports published by the National Amil Zakat Institute. The data analysis is: financial performance (financial ratio by Ritchie and Kolodinsky). Based on the calculation, the result of the study state, BAZNAS is the highest-performing Amil Zakat Institution in the financial performance category due to its high fiscal performance ratios and its strong financial management capabilities, which maximize the amount of funds distributed in accordance with what was collected from the funds that were successfully collected. When it comes to the total amount of money collected over the course of 12 years, Dompet Dhuafa performs better than BAZNAS.